Expression of Epidermal Growth Factor Receptor (Egfr) in Mole Hydatidiforms, Exaggarated Placental Sites and Normal Placentas and Ki 67 in Mole Hydatidiforms and Normal Placentas - Gökben Yıldırım Küpesiz; Hadice Elif Peştereli; Gülgün Erdoğan; Mehmet Şimşek; Fatma Şeyda Karaveli (Medical Network, 2006)
OBJECTIVE: The aim of this study is to find out differences between expression of EGFR (epidermal growth f actor receptor) and Ki 67 labeling index (LI) in complete, incomplete mole hydatidiforms, exaggareted placental sites and normal placentas. STUDY DESIGN: Eighteen incomplete, 7 complete hy datidif orm moles, 19 exaggareted placental sites and 10 placentas (control group) were studied immunohistochemically for EGFR (epidermal growth f actor receptor)and Ki 67. RESULTS: Ki 67 LI of villous cytotrophoblasts differed significantly between complete and incomplete hydatidiform moles (p < 0.01). Ki67 LIs of hydatidiform moles were significantly higher than control group (p < 0.001). EGFR (epidermal growth factor receptor)staining of villous cytotrophoblasts differed signif icantly between complete, incomplete hydatidiform moles and control group (p < 0.001). EGFR (epidermal growth f actor receptor) expression of syncytiotrophoblast differed signif icantly between complete, incomplete hydatidiform moles and control group (p < 0.001). CONCLUSION: Expression of EGFR (epidermal growth f actor receptor)in syncytiotrophoblast and cy totrophoblasts is important in the pathogenesis of complete and incomplete hydatidiform moles. Ki67 LI can be a useful marker in differentiating complete and incomplete moles.